4
$\begingroup$

For all $a, b, c>0$ and $a+b+c=3$ Prove that $$ \sqrt{\frac{a}{b+3} } +\sqrt{\frac{b}{c+3} } +\sqrt{\frac{c}{a+3} } \leq \frac{3}{2} $$ I tried cauchy-schwarz inequality for the L. H. S like and I get $ [\left( \sqrt{a} \right) ^{2}+\left( \sqrt{b} \right) ^{2}+\left( \sqrt{c} \right) ^{2}]\left[ \left( \frac{1}{\sqrt{b+3} } \right) ^{2}+\left( \frac{1}{\sqrt{c+3} } \right) ^{2}+\left( \frac{1}{\sqrt{a+3} } \right) ^{2}\right] \geq \left( \frac{\sqrt{a} }{\sqrt{b+3} } +\frac{\sqrt{b} }{\sqrt{c+3} } +\frac{\sqrt{c} }{\sqrt{a+3} } \right) ^{2}$ Then I get by AM-GM the maximum value of $abc=1$ and the inequality have the value 3... How I can prove inequality?.

$\endgroup$
  • $\begingroup$ @user236182 yes. I edited the question $\endgroup$ – user260699 Nov 27 '15 at 18:37
  • $\begingroup$ The C-S approach won't work. The $LHS$ that you got is too large. Let $(a,b,c)=(2,0.5,0.5)$. Then $\sqrt{[\left( \sqrt{a} \right) ^{2}+\left( \sqrt{b} \right) ^{2}+\left( \sqrt{c} \right) ^{2}]\left[ \left( \frac{1}{\sqrt{b+3} } \right) ^{2}+\left( \frac{1}{\sqrt{c+3} } \right) ^{2}+\left( \frac{1}{\sqrt{a+3} } \right) ^{2}\right]} >\frac{3}{2}$ $\endgroup$ – user236182 Nov 27 '15 at 18:47
  • $\begingroup$ @user236182 so could you tell me a little hint? $\endgroup$ – user260699 Nov 27 '15 at 19:07
  • $\begingroup$ @user260699 Could you share the source of this problem? Thanks. $\endgroup$ – Kay K. Nov 29 '15 at 15:01
5
$\begingroup$

First, we use Cauchy-Schwartz inequality: $$ A^2=\left(\sqrt{\frac{a}{b+3} } +\sqrt{\frac{b}{c+3} } +\sqrt{\frac{c}{a+3} }\right)^2 =\\ \left(\sqrt{\frac{a}{(a+3)(b+3)}(a+3) } +\sqrt{\frac{b}{(b+3)(c+3)} (b+3)} +\sqrt{\frac{c}{(c+3)(a+3)}(c+3) }\right)^2 \leq \\ \left({\frac{a}{(a+3)(b+3)} } +{\frac{b}{(b+3)(c+3)} } +{\frac{c}{(c+3)(a+3)} }\right)\times (a+3+b+3+c+3) . $$ Since $a+3+b+3+c+3=12$, it is enough to prove: $$ \left({\frac{a}{(a+3)(b+3)} } +{\frac{b}{(b+3)(c+3)} } +{\frac{c}{(c+3)(a+3)} }\right)\leq \frac 3{16}. (\star) $$ From this step on, I went the ugly way, since the manipulation was not so frightening. With a simple and nice proof of this step, the whole proof would become much easier.

Anyway, after the simple multiplications, we get to the following inequality: $$ 18-7(ab+ac+bc)+3abc\geq 0. $$ This can be further simplified, using the fact such as $a^2+b^2+c^2=9-2(ab+ac+bc)$ and using the famous following identity: $$ a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-ac-bc). $$ We can further simplify the inequality to the following: $$ a^3+b^3+c^3\geq a^2+b^2+c^2. $$ This follows from the following steps:

  1. Cauchy-Schwartz: $(a+b+c)(a^3+b^3+c^3)\geq (a^2+b^2+c^2)^2 \implies 3(a^3+b^3+c^3)\geq (a^2+b^2+c^2)^2$
  2. Cauchy-Schwartz: $(1+1+1)(a^2+b^2+c^2)\geq (a+b+c)^2 \implies (a^2+b^2+c^2)\geq 3.$
  3. Combine two previous steps: $$ 3(a^3+b^3+c^3)\geq (a^2+b^2+c^2)^2\geq 3(a^2+b^2+c^2). $$ And therefore, this proves $(\star)$.
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.